Global patterns of interaction specialization in bird– flower networks - Zanata, Thais B.; Dalsgaard, Bo; Passos, Fernando C.; Cotton, Peter A.; Roper, James J.; Maruyama, Pietro K.; Fischer, Erich; Schleuning, Matthias; González, Ana M. Martín; Vizentin-Bugoni, Jeferson; Franklin, Donald C.; Abrahamczyk, Stefan; et al. (Blackwell Publishing Inc., 2017)
Aim: Among the world’s three major nectar-feeding bird taxa, hummingbirds are the most phenotypically specialized for nectarivory, followed by sunbirds, while the honeyeaters are the least phenotypically specialized taxa. We tested whether this phenotypic specialization gradient is also found in the interaction patterns with their floral resources.